The Philippines yearbook, 2006. (Fookien Times Yearbook, 2006)
These 328 pages of the Philippines Yearbook 2006 present its values theme from various angles to political viewpoints. It features essays, bible verses and anecdotes written by some of our country's top opinion writers regarding the theme. It includes the updated business data of the top 500 corporations and listing of government and foreign embassies.